PENGARUH LINGKUNGAN PERGAULAN DAN MEDIA SOSIAL TERHADAP PERILAKU KONSUMTIF MAHASISWA PENDIDIKAN EKONOMI FKIP UNTAN - Amaliah, Rizky; Achmadi, Achmadi; Syamsuri, Syamsuri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
The purpose of this study was to analyze the influence of social environment and social media on the consumptive behavior of students. The method used is a relationship and correlation study with a quantitative approach. The population of this study were economics education students in the 2021-2023 batch. The total population was 177 students with a sample of 64 students. Non-random sampling technique using purposive sampling method. Data analysis using multiple linear analysis. The independent variables of the study are social environment (X1), social media (X2), and the dependent variable is consumptive behavior (Y). Partial t test results 1). There is a partial influence between the social environment (X1) on consumptive behavior (Y) with a sig value of 0.008 0.05: 2). There is no partial influence between social media (X2) on consumptive behavior (Y) with a sig value of 0.640 0.05. The results of the F test simultaneously obtained a sig value of 0.003 0.05, this indicates that the social environment (X1) and social media (X2) simultaneously affect consumptive behavior (Y). The test results of the coefficient of determination R Square (R ²) obtained a value of 0.169, which means that the social environment (X1) and social media (X2) have a low influence on consumptive behavior (Y), which is 16.9%.